2008
DOI: 10.1021/ic702141h
|View full text |Cite
|
Sign up to set email alerts
|

Acetonitrile-Vapor-Induced Color and Luminescence Changes in a Cyclometalated Heteroleptic Iridium Complex

Abstract: An iridium complex PIr(qnx) (iridium(III) bis(2-phenylpyridinato-N,C(2))(quinoxaline-2-carboxylate)) is reported for its unique and fast vapochromic and vapoluminescent behaviors. The emission of PIr(qnx) is governed by the whole crystal rather than the individual molecule. PIr(qnx) has been found to exist as both black and red forms in the solid state. The black form can be transformed into the red form upon its exposure to acetonitrile or propiononitrile vapor, whereas no response was observed when it was ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 30 publications
0
28
0
Order By: Relevance
“…[4][5][6] Thus, Ir III complexes have been widely studied for many applications including organic light-emitting diodes (OLEDs), [7][8][9][10][11] light-emitting electrochemical cells (LECs), [12] luminescence sensitizers, [13,14] biological labeling, [15,16] and chemosensors. [16][17][18][19][20][21] In pursuit of a highly emissive Ir III complex, many heteroleptic complexes of the type [Ir(C^N) 2 MLCT transitions. In such cases, density functional theory calculations indicate that the highest occupied molecular orbital (HOMO) is largely metal-centered, whereas the lowest unoccupied molecular orbital (LUMO) is primarily localized on the heterocyclic rings of the cyclometalated ligands.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Thus, Ir III complexes have been widely studied for many applications including organic light-emitting diodes (OLEDs), [7][8][9][10][11] light-emitting electrochemical cells (LECs), [12] luminescence sensitizers, [13,14] biological labeling, [15,16] and chemosensors. [16][17][18][19][20][21] In pursuit of a highly emissive Ir III complex, many heteroleptic complexes of the type [Ir(C^N) 2 MLCT transitions. In such cases, density functional theory calculations indicate that the highest occupied molecular orbital (HOMO) is largely metal-centered, whereas the lowest unoccupied molecular orbital (LUMO) is primarily localized on the heterocyclic rings of the cyclometalated ligands.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al [361] reported a vapoluminescent cyclometalated heteroleptic iridium complex [iridium(III)-bis(2-phenylpyridinato-N,C2)(quinoxaline-2-carboxylate); PIr(qnx)] that was synthesized into two forms (black and red forms). The black form is weakly luminescent at 692 nm, with a short lifetime of 43 ns.…”
Section: Photoluminescence Sensingmentioning
confidence: 99%
“…Photoluminescence spectra of the black form exposed to acetonitrile vapor at different periods of time. Reproduced with permission from [361]. …”
Section: Figurementioning
confidence: 99%
“…10) shows selective vapochromic and vapoluminescent properties in response to acetonitrile or propiononitrile vapour, while remaining unchanged for other VOCs [105]. Crystals of the compound change from a black to a red polymorph in less than 1 min on exposure to the solvent vapours; at the same time, strong emission is switched 'on' (red form).…”
Section: Detection Of Gases and Volatile Organic Compoundsmentioning
confidence: 99%